2012
DOI: 10.1590/s1517-83822012000100034
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological biodiversity in poultry and paddy straw wastes in composting systems

Abstract: Immense quantity of waste is generated in association with poultry meat egg and crop production. The potential risks due to disposal of these wastes are magnified as a result of dense refinement of poultry production and the decreasing amount of land available for waste disposal. The study aims at studying the microbiological biodiversity of poultry waste and paddy straw based co-composting system. The predominant microflora of the poultry manure were bacteria, fungi, enteric bacteria and spore forming bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 6 publications
3
10
2
1
Order By: Relevance
“…This is mainly because of higher surface area and porosity. Similar results were reported by Devi et al, (2012). The poultry manure was rich in nitrogen (2.85 %) and the total P, K, Ca, Mg and sulphur contents were 1.56, 1.69, 2.89, 1.23 and 0.50 per cent respectively which could be supported by the results of Mohamed et al, (2010).…”
Section: Resultssupporting
confidence: 89%
“…This is mainly because of higher surface area and porosity. Similar results were reported by Devi et al, (2012). The poultry manure was rich in nitrogen (2.85 %) and the total P, K, Ca, Mg and sulphur contents were 1.56, 1.69, 2.89, 1.23 and 0.50 per cent respectively which could be supported by the results of Mohamed et al, (2010).…”
Section: Resultssupporting
confidence: 89%
“…Biostimulation as a strategy of enhancing lignocellulose degradation can be achieved using animal manure that provides extra nutrients to microbial decomposers (Higashikawa et al 2010;Lim et al 2015). Livestock manure is actually known to harbour microorganisms that are important for composting and for soil development (Devi et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, high fungi distribution observed at the mesophilic phase may possibly be attributed to the relatively high moisture content around the compost since fungi as saprophytes form more colonies in moist environment than dry environment (Srivastava et al 2011). Actinomycete count recorded during the cooling-stabilization phase was highest possibly due to its primary metabolic role in oxidation of recalcitrant materials such as lignin and cellulose during agricultural waste composting (Yu et al 2007;Partanen et al 2010;Devi et al 2012;Limaye et al 2017). Hence, the diversity of microbial community in compost underpins the role of microbes in the monitoring of co-composting process for nutrient-rich and high-quality product.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies (Yu et al 2007;Partanen et al 2010) revealed that microbial number and the level of activity changed during composting leading to heat generation that exert adverse effects on the diversity and distribution of mesophiles. Although few bacteria are reported to be thermo-tolerant, most were more active under cool environment (Devi et al 2012). The least bacteria and fungi counts were recorded during thermophilic phase possibly due to dormancy and differential responses to compost temperature (Huhe et al 2017).…”
Section: Discussionmentioning
confidence: 99%